RASIONALITAS IBNU RUSYD DAN RELEVANSINYA DALAM MEMBANGUN IDENTITAS MELAYU ISLAM DI RIAU - Harianto, Alpin; Anna, Dian Nur (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2025)
This study is motivated by the importance of examining the relevance of the Muslim philosopher Ibn Rushd’s thought in shaping the Islamic Malay identity in Riau, which is currently facing the challenges of globalization, modernization, and shifting cultural values. The main problem addressed in this research is how Ibn Rushd’s concept of rationality is understood and integrated into the formation of religious and cultural character within the Islamic Malay community in Riau. This research employs a library research method by analyzing Ibn Rushd’s works alongside scholarly literature related to the Islamic Malay identity. The findings reveal that Ibn Rushd’s idea of harmonizing reason and revelation aligns with the principle of “adat bersendikan syarak, syarak bersendikan Kitabullah” in the Riau Malay tradition. The rationality promoted by Ibn Rushd strengthens the intellectual framework of the Islamic Malay community, fostering a more moderate, critical, and responsive attitude toward contemporary challenges. In conclusion, Ibn Rushd’s thought significantly contributes to constructing an Islamic Malay identity rooted in Islamic values while remaining open to knowledge and modern intellectual developments. Keyword : Ibn Rushd, Rationality, Riau Malay Identity